Tributación y escenarios locales en el centro de la península ibérica: algunas hipótesis a partir del análisis de las pizarras «visigodas» - Martín Viso, Iñaki (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2007)
Abstract The “Visigothic” slates are a group of texts that have been found in different archaeological sites of the central part of Iberian Peninsula. Although they are one of the rare remains of late antique private documentation, there is not any social analysis of them, due to the problems of their interpretation. In spite of this, some philological works has been carried out, making some aspects about the language and culture clear. This paper tries to achieve a first approach to a social explanation of the slates through three hypothesis: the tributary meaning of great part of the pieces, the connection of the remains with some intermediate places of the countryside and the view of the slates as a trace of the implementation of channels that linked the central authority with the local powers.